Risk factors for loco-regional recurrence after radical cystectomy of muscle-invasive bladder cancer: A systematic-review and framework for adjuvant radiotherapy. (November 2018) - Sargos, Paul; Baumann, Brian C.; Eapen, Libni; Christodouleas, John; Bahl, Amhit; Murthy, Vedang; Efstathiou, Jason; Fonteyne, Valérie; Ballas, Leslie; Zaghloul, Mohamed; Roubaud, Guilhem; Orré, Mathieu; et al.
Highlights: Relapse after radical cystectomy is correlated with a poor prognosis, without any clear impact of perioperative chemotherapy. LRR patterns are well-known and with predictive factors identified. In this direction, prospective trials evaluating safety and efficacy of adjuvant radiotherapy are ongoing. Abstract: Background: Radical cystectomy (RC) associated with pelvic lymph node dissection (PLND) is the most common local therapy in the management of non-metastatic muscle invasive bladder cancer (MIBC). Loco-regional recurrence (LRR), however, remains a common and important therapeutic challenge associated with poor oncologic outcomes. We aimed to systematically review evidence regarding factors associated with LRR and to propose a framework for adjuvant radiotherapy (RT) in patients with MIBC. Methods: We performed this systematic review in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines. We searched the PubMed database for articles related to MIBC and associated treatments, published between January 1980 and June 2015. Articles identified by searching references from candidate articles were also included. We retrieved 1383 publications from PubMed and 34 from other sources. After an initial screening, a review of titles and abstracts, and a final comprehensive full text analysis of papers assessed for eligibility, a final consensus on 32 studies was obtained. Results: LRR is associated with specific patient-, tumor-, center- or treatment-related variables. LRR varies widely, occurring in as many as 43% of the cases and is strongly related to survival outcomes. While perioperative treatment does not impact on LRR, pathological factors such as pT, pN, positive margins status, extent of PLND, number of lymph nodes removed and/or invaded are correlated with LRR. Patients with pT3-T4a and/or positive lymph-nodes and/or limited pelvic lymph-node dissection and/or positive surgical margins have been distributed in LRR risk groups with accuracy. Conclusions: LRR patterns are well-known and for selected patients, adjuvant treatments could target this event. Intrinsic tumor subtype may guide future criteria to define a personalized treatment strategy. Prospective trials evaluating safety and efficacy of adjuvant RT are ongoing in several countries.